(untitled) (Praxis Educativa, 2014)
Can education change society? It is one of the main questions to be asked in neoliberal and neoconservative times in favor of a democratic education. Part of the task of the critical-academic activist is to make public the challenges to the conservative modernization, advocating anti-hegemonic practices by giving his or her own testimony or that of other colleagues, regarding the possibility of taking steps toward building a reconstituted public sphere within the spaces in which we live and work.